GLOBALISATION AND UNIFIKATION - Petrov , Aleksandar (E-Journal VFU, 2025)
The article examines aspects of globalization from the point of view of individual psychology on the one hand, and on the another - from the society itself, viewed as a role structure. Topics related to the socio-economic and political aspects of globalization have been deliberately avoided, mainly because there is already too much talk in this direction, but also because of an attempt to pay attention to aspects of social dynamics in its basic field of genesis - the interaction between the personallity and the community. It opens the way to a discussion regarding the operation of structures showing similarity at different levels - "inorganic", "organic", "social". An own dynamic of society towards a global structure is argued.